Role of human epicardial adipose tissue–derived miR-92a-3p in myocardial redox state - Carena, MC; Badi, I; Polkinghorne, M; Akoumianakis, I; Psarros, C; Wahome, E; Kotanidis, CP; Akawi, N; Antonopoulos, AS; Chauhan, J; Douglas, G; Channon, KM; et al. (Elsevier, 2023)
Background Visceral obesity is directly linked to increased cardiovascular risk, including heart failure.